2010
DOI: 10.1111/j.1600-6143.2010.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Transcripts and NK Cells in Kidney Biopsies from Patients with Donor-Specific Antibodies: Evidence for NK Cell Involvement in Antibody-Mediated Rejection

Abstract: To explore the mechanisms of antibody-mediated rejection (ABMR) in kidney transplants, we studied the transcripts expressed in clinically indicated biopsies from patients with donor-specific antibody (DSA). Comparison of biopsies from DSA-positive versus DSAnegative patients revealed 132 differentially expressed transcripts: all were associated with class II DSA but none with class I DSA. Many transcripts were expressed in DSA-positive ABMR but were also expressed in T-cell-mediated rejection (TCMR), reflectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
330
5
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(368 citation statements)
references
References 41 publications
20
330
5
13
Order By: Relevance
“…The Edmonton group showed that the biopsy specimens from DSA+ patients displayed three molecular phenotypes: upregulation of ENDAT (24), NKAT (25), and GRIT (26), similar to our findings. IFN-g secreted by T cells and NK cells is essential for induction of class I and II antigens on endothelium and increases antibody binding to the endothelium, which is followed by complement fixation to induce allograft inflammation and injury.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The Edmonton group showed that the biopsy specimens from DSA+ patients displayed three molecular phenotypes: upregulation of ENDAT (24), NKAT (25), and GRIT (26), similar to our findings. IFN-g secreted by T cells and NK cells is essential for induction of class I and II antigens on endothelium and increases antibody binding to the endothelium, which is followed by complement fixation to induce allograft inflammation and injury.…”
Section: Discussionsupporting
confidence: 81%
“…Hidalgo et al studied the gene expression profiles of biopsy specimens with AMR and identified 23 selective gene transcripts in AMR (DSAST) but not cellular rejection (25). Six of those 23 genes showed selective high expression in NK cells and 8 were primarily expressed in endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…A set of transcripts (DSA‐specific transcripts [DSASTs]) was determined to be differentially expressed in renal allograft biopsies from DSA‐positive versus ‐negative patients 29, a finding that was later confirmed independently at a different center 30. Consequently, DSASTs have the potential to identify cases of ABMR in patients with non‐detectable HLA DSA.…”
Section: Dsa Against Hla or Other Antigens In The Diagnosis Of Abmrmentioning
confidence: 99%
“…Generating consensus for sets of molecules or classifiers reflecting certain biological or disease processes related to the established histologic Banff lesions would enable us to assess and validate their clinical value. In this regard, the most robust evidence is currently available for the association among antibody‐mediated injury; microcirculation inflammation; and increased expression of endothelial, NK cell, and inflammation‐associated transcripts in the allograft 29, 54, 55.…”
Section: Prospects For Adopting Molecular Pathology In Renal Allografmentioning
confidence: 99%
“…In solid organ transplant patients, acute CMV infection increases the CD57+ NKGDC hi (memory phenotype) pool, which appears to be CMV specific (179). The effects of CMV and NK cells in the setting of MHC-mismatched grafts are linked to coronary vasculopathy and renal graft injury (180)(181)(182)(183)(184)(185)(186)(187)(188). In part, this is mediated by cytokine-mediated stimulation of alloreactive T cells and by direct alloimmune injury (156).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%